Application of linked data technologies in libraries: Pakistani information professionals' attitudes and perceptions. Issue 5 (26th November 2020) - Warraich, Nosheen Fatima; Rorissa, Abebe
Abstract : Purpose: This study aims to ascertain the information professionals' perceptions and attitudes towards the application of linked data (LD) technologies in libraries in the context of a developing country. It also explores the Pakistani information professionals' level of familiarity with LD concepts, plans and efforts in its application, along with its potential benefits. Design/methodology/approach: An online questionnaire survey was used to identify the information professionals' perceived level of familiarity with LD concepts and benefits to implement LD in libraries, and their plans and efforts to adopt LD technologies. A questionnaire was developed to meet the objective of the study and collect data from the purposefully selected professionals ( N = 86) working in university libraries in Pakistan. SPSS was used to analyse the data set. Findings: Findings show that LD application in libraries is still not common among Pakistani information professionals. They have a moderate level of understanding with semantic Web (SW) and LD key concepts. The respondents were positive about the potential benefits of implementing LD technology in libraries, such as assisting patrons to discover relevant information, enriching traditional bibliographic records, enhancing the visibility and discoverability of library data and improving the users' overall search experiences that may foster future developments. Overall, the respondents' institutions were on different levels of planning – from working on a plan to having a finalized plan. The findings emphasized establishing the SW's potential in library services. Research limitations/implications: There are certain limitations of this study. Firstly, the population is Pakistani information professionals who are purposefully selected. Secondly, the findings reveal that the respondents' understanding with LD concepts, opinions about LD, plans and efforts to its application along with its potential benefits in libraries are self-perceived and not tested in any way and they were not actually implementing these technologies in their institutions because of a lack of best practices. It is a quantitative study and it will serve as a baseline study, even though there is a need to conduct more in-depth qualitative studies in the information environment to explore the phenomenon. Social implications: This study will guide information professionals and policymakers to take initiatives towards the implementation of LD technology in libraries. It may also lead to further research to understand the perceptions of information professionals so that appropriate training and advocacy programmes can be developed to promote LD initiatives in libraries. Originality/value: To the best of the authors' knowledge, this is the first known empirical study in the context of a developing country. It clearly demonstrates the Pakistani information professionals' perceptions regarding the library LD and associated plans along with potential benefits to implement it.